PHOTOSYNTHETICALLY ACTIVE RADIATION AND TRANSPIRATION INDICES OF TREES AND SHRUBS IN THE WALNUT FORESTS OF THE WESTERN TIEN SHAN (International journal of artificial intelligence, 2025)
This article studies the photosynthetically active radiation (PAR) and transpiration processes of various tree and shrub species in nut-bearing forests of the Western Tien Shan mountain range. The study analyzed the influence of climate, soil and microclimate factors on plant water exchange and photosynthesis processes. The results showed that light intensity and leaf temperature activate the transpiration process, while relative humidity of the air slows it down. It was noted that high temperature and low soil moisture negatively affected the development of seedlings. The results of the study are important as a scientific basis for ensuring the stability of forest ecosystems in mountainous areas and managing natural regeneration processes.